Interactive Reading Model in Enhancing Arabic Learners’ Reading Comprehension: Evidence from Islamic Boarding Schools - Muhammad Arisuddin; Jimmy Hasan Carter (Journal of Linguistic Metacognition and Language Learning, 2026)
Arabic reading comprehension requires more than word recognition because learners must manage morphological density, syntactic flexibility, and frequent omission of short vowels (harakāt), which can increase ambiguity and cognitive load. Therefore, this study investigates the efficacy of an interactive reading model in improving Arabic reading comprehension among students in an Indonesian pondok pesantren and examines how learners experience and negotiate reading difficulties during interactive reading. Using a qualitative case study design, the research involved 25 pesantren students who had studied Arabic for one to two years. Data were collected through semi-structured interviews and classroom observations to capture both students’ perceptions and their observable reading behaviors across pre-reading, while-reading, and post-reading phases. Thematic analysis was applied through iterative coding, codebook refinement, and category development to generate themes describing comprehension development, breakdown-and-repair processes, and cross-language differences in reading strategies. Findings indicate that interactive reading shifted students from predominantly word-for-word translation toward more meaning-oriented comprehension. Students reported improved ability to identify main ideas, select relevant details, and track cohesion through pronoun reference and discourse markers. Confidence in reading unvowelled texts increased because interactive routines normalized uncertainty and enabled collaborative clarification. When comprehension broke down, students commonly employed repair moves such as rereading for context, testing root-pattern clues, consulting peers, and seeking teacher scaffolding for confirmation. Compared with Indonesian reading, Arabic comprehension was slower and more form-focused, making rapid skimming and automatic inferencing difficult; however, interactive reading reduced these constraints by supporting negotiation of meaning through dialogue. The study contributes a context-sensitive account of how interactive reading can be integrated with pesantren literacy traditions to strengthen comprehension processes in classical and unvowelled Arabic texts.